Membangkitkan minat belajar Geografi dengan Google Earth pada peserta didik kelas XI IPS - Riyadi Riyadi (Perkumpulan Kualitama Edukatika Indonesia, 2021)
The purpose of this study was to determine interest in learning Geography in students of class XI IPS at SMAN 1 Karangrayung, to find out the positive impact of using Google Earth in learning Geography at SMAN 1 Karangrayung, and to arouse interest in learning Geography with Google Earth in class XI IPS at SMAN 1 Karangrayung. SMAN 1 Karangrayung. The place of this research is SMA Negeri 1 Karangrayung, Grobogan Regency. The subjects in this study were all students of class XI IPS in the academic year 2021/2022. The number of students in class XI IPS is 107 students consisting of 40 male students and 67 female students. The method in this Best Practice is to compare the data on interest in learning geography in the initial condition with data on interest in learning geography in the final condition. Data on interest in learning geography in the initial conditions were obtained from questionnaires given before students were introduced to Google Earth. Meanwhile, data on interest in learning geography in the final condition were obtained from questionnaires given after students were introduced to Google Earth and used Google Earth in learning geography. The results of this Best Practice show that the percentage of interest in learning geography for the high category in the initial condition is 5.61%, and in the final condition it is 99.07%. While the percentage of interest in learning geography for the low category in the initial condition was 94.39%, and in the final condition it was 0.93%. These results prove that Google Earth can generate interest in learning geography in class XI IPS students at SMAN 1 Karangrayung in 2021.